2020
DOI: 10.1002/1878-0261.12696
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering MET‐dependent modulation of global cellular responses to DNA damage by quantitative phosphoproteomics

Abstract: Increasing evidence suggests that interference with growth factor receptor tyrosine kinase (RTK) signaling can affect DNA damage response (DDR) networks, with a consequent impact on cellular responses to DNA-damaging agents widely used in cancer treatment. In that respect, the MET RTK is deregulated in abundance and/or activity in a variety of human tumors. Using two proteomic techniques, we explored how disrupting MET signaling modulates global cellular phosphorylation response to ionizing radiation (IR). Fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 92 publications
2
11
0
Order By: Relevance
“…Until now, it is not fully understood how c-MET is affecting radiosensitivity. A recently published study by Bensimon et al applied quantitative phosphoproteomic technique and identified a novel c-MET phospho-site that bears as substrate for the DNA damage response (DDR) machinery including DNA-dependent protein kinase (DNA-PK), nuclear mitotic apparatus protein 1 (NUMA1) and checkpoint kinase 1 (CHEK1) in c-MET addicted cancer cell lines [ 58 ]. We analyzed the DNA repair capacity of purified c-MET high and c-MET low cells within the c-MET-dependent cell line SAS and UT-SCC-5 using the yH2AX assay.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, it is not fully understood how c-MET is affecting radiosensitivity. A recently published study by Bensimon et al applied quantitative phosphoproteomic technique and identified a novel c-MET phospho-site that bears as substrate for the DNA damage response (DDR) machinery including DNA-dependent protein kinase (DNA-PK), nuclear mitotic apparatus protein 1 (NUMA1) and checkpoint kinase 1 (CHEK1) in c-MET addicted cancer cell lines [ 58 ]. We analyzed the DNA repair capacity of purified c-MET high and c-MET low cells within the c-MET-dependent cell line SAS and UT-SCC-5 using the yH2AX assay.…”
Section: Discussionmentioning
confidence: 99%
“…This was not totally unpredictable, as the Ser395 of NuMa is one of the hundreds of consensus sequences phosphorylated by ATM in response to irradiation [ 10 ]. Moreover, the phospho-proteomic analysis of EBC-1 cells treated with irradiation and MET inhibition showed the increased phosphorylation of NuMA [ 20 ]. NuMA is a key structural nuclear protein, that binds microtubules and plays a role in the formation and maintenance of the spindle poles and the alignment and segregation of chromosomes during mitotic cell division (for a review, see [ 44 ]).…”
Section: Discussionmentioning
confidence: 99%
“…This oncogene was named after its isolation as an oncogenic gene from an osteosarcoma cell line transformed in vitro by the chemical carcinogen methyl-nitro-nitroso-guanidine (MNNG) [ 18 ] and found deregulated and/or activated in a variety of human tumor types and serves as an oncogenic target (for a review, see [ 19 ]). Phosphoproteomic analysis of MET overexpressing cells after irradiation and treatment with METi revealed the modulation of several substrates of the DDR [ 20 ]. In line with these observations, MET inhibition was shown to sensitize glioblastoma cells to irradiation (IR) [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of ATM led to a decrease in the phosphorylation of 20 out of 32 putative PPM1D substrates (Figure 2E), suggesting that ATM, and not DNA-PK or ATR, is the main kinase phosphorylating PPM1D substrates in response to DSB induction. Upon ATM inhibition, the strongest decrease in phosphorylation was observed for the previously characterized ATM target NUMA1 (S395) (Bensimon et al, 2020) as well as for the poorly characterized protein Kanadaptin (SLC4A1AP; S709). Among the proteins with decreased phosphorylation upon ATM inhibition were also the previously described substrate ACIN1 (S243) (Bensimon et al, 2020) and the auto-phosphorylated residue of CHEK2 (S379) (Lovly et al, 2008), which acts downstream of ATM.…”
Section: Phosphorylation Signaling Upon Acute Double-strand Break Ind...mentioning
confidence: 99%
“…Upon ATM inhibition, the strongest decrease in phosphorylation was observed for the previously characterized ATM target NUMA1 (S395) (Bensimon et al, 2020) as well as for the poorly characterized protein Kanadaptin (SLC4A1AP; S709). Among the proteins with decreased phosphorylation upon ATM inhibition were also the previously described substrate ACIN1 (S243) (Bensimon et al, 2020) and the auto-phosphorylated residue of CHEK2 (S379) (Lovly et al, 2008), which acts downstream of ATM.…”
Section: Phosphorylation Signaling Upon Acute Double-strand Break Ind...mentioning
confidence: 99%